Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Transcriptomic analyses during development reveal mechanisms of integument structuring and color production - Adam M. M. Stuckert; Layla Freeborn; Kimberly A. Howell; Yusan Yang; Rasmus Nielsen; Corinne Richards-Zawacki; Matthew D. MacManes (Evolutionary Ecology, 2024)
Skin coloration and patterning play a key role in animal survival and reproduction. As a result, color phenotypes have generated intense research interest. In aposematic species, color phenotypes can be important in avoiding predation and in mate choice. However, we still know little about the underlying genetic mechanisms of color production, particularly outside of a few model organisms. Here we seek to understand the genetic mechanisms underlying the production of different colors and how these undergo shifting expression patterns throughout development. To answer this, we examine gene expression of two different color patches(yellow and green) in a developmental time series from young tadpoles through adults in the poison frog Oophaga pumilio. We identified six genes that were differentially expressed between color patches in every developmental stage ( casq1, hand2, myh8, prva, tbx3, and zic1). Of these, hand2, myh8, tbx3, and zic1 have either been identified or implicated as important in coloration in other taxa. Casq1 and prva buffer Ca 2+ and are a Ca 2+ transporter, respectively, and may play a role in preventing autotoxicity to pumiliotoxins, which inhibit Ca 2+ -ATPase activity. We identify further candidate genes (e.g., adh, aldh1a2, asip, lef1, mc1r, tyr, tyrp1, xdh ), and identify a suite of hub genes that likely play a key role in integumental reorganization during development (e.g., collagen type I–IV genes, lysyl oxidases) which may also affect coloration via structural organization of chromatophores that contribute to color and pattern. Overall, we identify the putative role of a suite of candidate genes in the production of different color types in a polytypic, aposematic species.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Inhibition of serotonin transporters disrupts the enhancement of fear memory extinction by 3,4-methylenedioxymethamphetamine (MDMA) - Matthew B. Young; Seth D. Norrholm; Lara M. Khoury; Tanja Jovanovic; Sheila A.M. Rauch; Collin M. Reiff; Boadie W. Dunlop; Barbara O. Rothbaum; Leonard L. Howell (Psychopharmacology, 2017)

Panel of synaptic protein ELISAs for evaluating neurological phenotype - Paul E. Gottschall; Joanne M. Ajmo; Autumn K. Eakin; Matthew D. Howell; Hina Mehta; Lauren A. Bailey (Experimental Brain Research, 2010)